Learning OpenCV 3 : computer vision in C++ with the OpenCV library - Kaehler, Adrian; Bradski, Gary R. (O'Reilly Media, 2016)
"This book provides a working guide to the C++ Open Source Computer Vision Library (OpenCV) version 3.x and gives a general background on the field of computer vision sufficient to help readers use OpenCV effectively."--Preface.